Model Peningkatan Akuntabilitas Keuangan melalui Optimalisasi Sistem Informasi Keuangan dan Kompetensi Aparatur Desa - Puspitawati, Lilis; Amanda, Kintan; Surtikanti, Surtikanti (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This research aims to test the financial system optimization model and apparatus competency to increase village financial accountability. This research is motivated by an obstacle in the use of the financial system which is not yet optimal because it is predicted that there are still many village officials who are not yet able to use it. Descriptive and verification methods were used to test the model. This research came from 351 members of the population consisting of heads of financial affairs or financial operators in the Village Government in Tasikmalaya Regency. Sampling was carried out using a non-probability sampling technique with a purposive sampling method with the criteria of a village government that had implemented a village financial system (Siskeudeus), so the sample size in this study was 56 villages. Each village is represented by one sample person to be used as a respondent. The results of this research show that the village financial system is in good condition, ready to be used, and statistically has a significant positive effect on financial accountability. Different results were found in that the competence of village officials was deemed inadequate in the attitude category, so that this condition reduced the level of village financial accountability.